2021
DOI: 10.1021/acs.jpcc.1c07795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Large-Size A-Site Cation on the Crystal Growth and Phase Distribution of 2D/3D Mixed Perovskite Films via a Low-Pressure Vapor-Assisted Solution Process

Abstract: In this study, various concentrations of the largesized cation iodide, namely, phenylethylammonium iodide (PEAI), incorporated in lead iodide (PbI 2 ) solid films react with heated methylammonium iodide (MAI) to fabricate 2D/3D mixed perovskite films with vertical phase distribution, which are prepared by the low-pressure vapor-assisted solution process (LP-VASP). The 2D/3D mixed perovskite films exhibit multiple photoluminescence (PL) emissions that correspond to a 2D Ruddlesden−Popper layered perovskite of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…The lower-energy PL tail of low-dimensional perovskite material comes from the radiative recombination of trap states and/or strong phonon coupling with the distorted soft crystal structure. A recent report by Chen et al suggested that PL peaks at 540, 580, 620, 680, and 700 nm in PEAI–MAPbI 3 mixed perovskites were assumed to be n = 1, 2, 3, 4, and 5, respectively. The n -value of the RP phase in the PEAI–MAPbI 3 mixed perovskite can be tuned by the reaction temperature . However, the PL spectra of our measurements do not match the high n values of the reported values.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…The lower-energy PL tail of low-dimensional perovskite material comes from the radiative recombination of trap states and/or strong phonon coupling with the distorted soft crystal structure. A recent report by Chen et al suggested that PL peaks at 540, 580, 620, 680, and 700 nm in PEAI–MAPbI 3 mixed perovskites were assumed to be n = 1, 2, 3, 4, and 5, respectively. The n -value of the RP phase in the PEAI–MAPbI 3 mixed perovskite can be tuned by the reaction temperature . However, the PL spectra of our measurements do not match the high n values of the reported values.…”
Section: Resultscontrasting
confidence: 72%
“…The n-value of the RP phase in the PEAI−MAPbI 3 mixed perovskite can be tuned by the reaction temperature. 41 However, the PL spectra of our measurements do not match the high n values of the reported values. Our measurement data showed that n = 1 is observed at 510 nm and n = 2 is observed at ∼590 nm, but no peaks related to high n-values are observed around 620−700 nm.…”
Section: Optical Properties With Respect To 2d Perovskite Ratiosmentioning
confidence: 99%
“…Additional low-intensity peaks are also present at 22.5°and 26.5°in the 80 and 100 °C samples, which are ascribed to the presence of PEAI. 50 When the conversion temperature was further increased to 120 °C, the periodic peaks of the 2D perovskite disappeared, with only a low-intensity PbI 2 (100) peak present, which can be associated with an elevated temperature that results in the sublimation of PEAI from the 2D perovskite and/or the decomposition of the 2D perovskite.…”
Section: Structural Properties and Morphologymentioning
confidence: 99%
“…Furthermore, 2D/3D mixed perovskite films were developed using a low-pressure VASP, where phenylethylammonium iodide (PEAI) was added in PbI 2 and then the prepared film was reacted with methylamine (CH 3 NH 2(g) and MA (g) vapors). 151 It was demonstrated that the 3D MAPbI 3 perovskite was formed on the surface of multiple 2D RP perovskite layers of PEA 2 MA n −1 Pb n X3 n +1 with different n values, suggesting a vertical-gradient phase distribution, which could be effectively applied in perovskite optoelectronic devices. Moreover, quasi-2D PEA 2 (FAPbBr 3 ) n −1 PbBr 4 films prepared through the VASP were incorporated in perovskite light-emitting diodes, exhibiting not only high luminance and external quantum efficiency, but also good reproducibility.…”
Section: Synthetic Approaches For Polycrystalline Perovskite Filmsmentioning
confidence: 99%